2021
DOI: 10.1002/elan.202100172
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cu2+ Reduction and Nanoparticle Nucleation at Micro‐scale 1,2‐Dichlorobenzene‐water Interface Studied by Cyclic Voltammetry and Square‐wave Voltammetry

Abstract: Reduction and nanoparticle nucleation of Cu 2+ by decamethylferrocene was studied with cyclic and square-wave voltammetry at a microscale liquid-liquid interface established at the tip of a micropipette. With square-wave voltammetry, two reduction steps could be distinguished as two separate current waves. Comparing the experimental results of cyclic voltammetry with finite element method simulations, particle growth could be observed as an increasing limiting current. Furthermore, kinetic parameters could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Lehane et al 4 also recently employed a large w|DCE interface in the electropolymerization of PEDOT with Ce 4+ as oxidant/electron acceptor in the aqueous phase. Moreover, electrodeposition of Cu, Au, Pd, and Pt NPs at large 16 , 30 , 38 , 40 , 45 and micro 27 , 39 interfaces have been demonstrated previously using metallocenes as electron donors dissolved in oil.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Lehane et al 4 also recently employed a large w|DCE interface in the electropolymerization of PEDOT with Ce 4+ as oxidant/electron acceptor in the aqueous phase. Moreover, electrodeposition of Cu, Au, Pd, and Pt NPs at large 16 , 30 , 38 , 40 , 45 and micro 27 , 39 interfaces have been demonstrated previously using metallocenes as electron donors dissolved in oil.…”
Section: Resultsmentioning
confidence: 89%
“…In their work, they emphasized the absence of defect sites that are common at a solid/solution interface; thus, there is a large thermodynamic barrier to particle formation at ITIES. Nevertheless, they 38 and others 8 , 15 18 , 20 , 23 , 24 , 27 , 28 , 39 , 40 were able to experimentally demonstrate electrochemically controlled metal NP nucleation at w|o interfaces. Interestingly, Nishi’s group has suggested that the molecular structure of the liquid|liquid interface is transcribed onto the NP framework 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the liquid|liquid interface, or immiscible interface between two electrolyte solutions (ITIES), has become of increasing interest as a platform for the electrodeless synthesis of a variety of materials [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. While at first this relied on spontaneous chemical reactions, increasingly, electrochemical control via an applied external potential is being turned to.…”
Section: Introductionmentioning
confidence: 99%
“…Soon after, Johans et al [20][21][22][23] began investigating the thermodynamics of nanoparticle generation at an interface with seemingly few nucleation sites. TOAAuCl 4 is a special case and most contemporary studies have employed a hydrophilic metal salt (e.g., KAuCl 4 or CuSO 4 ), paired with a hydrophobic electron donor (e.g., ferrocene (Fc) [14,15] or decamethylferrocene [16]).…”
Section: Introductionmentioning
confidence: 99%